2006
DOI: 10.1017/s1431927606160328
|View full text |Cite
|
Sign up to set email alerts
|

Welcome form the Program Committee

Abstract: Microscopy and Microanalysis 2006 will be the premiere meeting of the year for scientists and technologists interested in learning about the latest advances in applications and techniques for the analysis of a broad range of materials in the biological and physical sciences, as well as nano- and bio-technology. M&M-2006 will again host the largest commercial exhibition of microscopy and microanalysis equipment and related accessories in the world. In addition to the usual sponsoring societies, the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Focused ion beam scanning electron microscopy (FIB SEM) has been used to produce high resolution 3D imaging of biological samples at 2 nm -5 nm lateral resolution and 20 nm -30 nm in axial resolution [2,3]. Additionally, FIB SEM combined with energy dispersive x-ray spectrometry (EDS) can provide 3D elemental information about the sample [4,5]. This ability to collect SEM resolution 3D structural data supplemented by chemical information can greatly enhance our understanding of biological processes.…”
mentioning
confidence: 99%
“…Focused ion beam scanning electron microscopy (FIB SEM) has been used to produce high resolution 3D imaging of biological samples at 2 nm -5 nm lateral resolution and 20 nm -30 nm in axial resolution [2,3]. Additionally, FIB SEM combined with energy dispersive x-ray spectrometry (EDS) can provide 3D elemental information about the sample [4,5]. This ability to collect SEM resolution 3D structural data supplemented by chemical information can greatly enhance our understanding of biological processes.…”
mentioning
confidence: 99%
“…More recently, the introduction of DualBeam 3D-EBSD has allowed for a better understanding of grain shape and size distribution, for better material performance prediction [5]. Some early work on the study of complex localized corrosion has also nicely demonstrated the potential of DualBeam 3D chemical analysis [6].…”
mentioning
confidence: 99%